2012
DOI: 10.4172/2161-1068.1000123
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Alcohol Use on the Clinical Presentation of Tuberculosis

Abstract: Objective: We examined whether patients with alcohol use who become ill with tuberculosis are more likely to develop cavitary disease than patients without a history of alcohol use.Methods: Chi-square tests were used to test for differences in the distribution of alcohol users between cavitary patients and non-cavitary patients. Logistic regression was performed to obtain adjusted odds ratios (OR) and 95% confidence intervals (CI). An interaction between homelessness and alcohol use was also tested.Results: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Whether alcohol may have an antagonistic, additive, or synergistic effect with these comorbidities or with other demographics is unclear. The four previous studies [ 9 11 , 33 ] that investigated alcohol and TB disease severity were in populations where women consume alcohol; one study reported 15% of those who consumed alcohol were female [ 10 ] compared to <1% in our cohort. Similarly, only one study reported comorbid diabetes [ 33 ]; 19% of their cohort had diabetes compared to 34% of our cohort.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Whether alcohol may have an antagonistic, additive, or synergistic effect with these comorbidities or with other demographics is unclear. The four previous studies [ 9 11 , 33 ] that investigated alcohol and TB disease severity were in populations where women consume alcohol; one study reported 15% of those who consumed alcohol were female [ 10 ] compared to <1% in our cohort. Similarly, only one study reported comorbid diabetes [ 33 ]; 19% of their cohort had diabetes compared to 34% of our cohort.…”
Section: Discussionmentioning
confidence: 81%
“…Researchers previously hypothesized that heavy alcohol use would be associated with infectiousness among TB patients due to increased cavitation and a higher likelihood of smear-positivity [ 10 , 32 ]. Previous studies found an approximately 25% increased risk of cavitation among those who use alcohol and a similar increased risk of smear positivity [ 9 10 ] However, these studies were done in low-burden settings and only one assessed alcohol use with a validated instrument. The only prior study which used standardized questionnaires for frequency and quantity of alcohol consumption found no independent relationship between recent alcohol use or lifetime alcohol use and lung cavitation at the time of TB diagnosis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those with AUD and TB are more likely to present with pulmonary rather than extrapulmonary TB ( 25 , 26 ). More of their lungs are affected by TB and they are predisposed to advanced, cavitary disease at the time of presentation ( 25 , 26 , 35 , 37 ).…”
Section: Alcohol and Tb Epidemiologymentioning
confidence: 99%
“…More recent studies have confirmed the increased risk of TB among persons with AUD and found that the latter is an independent risk factor for TB even after controlling for confounders such as comorbidities, lifestyle, or social determinants of health (Imtiaz et al, 2017; Lonnroth et al, 2008; Rehm et al, 2009). Further, those with AUD and TB are more infectious and have more clinically severe TB, including more cavitary disease and larger areas of the affected lung, compared to those without AUD (Classen et al, 1999; Diel et al, 2004; Fiske et al, 2009; Volkmann et al, 2015; Wang & Lauzardo, 2012). Even when treated, AUD is associated with poor outcomes, including increased risk of treatment failure and death (Ragan et al, 2020; Thomas et al, 2019; Volkmann et al, 2015).…”
Section: Introductionmentioning
confidence: 99%